Everyone Loves a Dog Story: Narratives of Urban Animal Welfare Policy. (13th May 2017) - Krcatovich, Erin Marie-Sergison; Reese, Laura A
Abstract: Public policy related to animal issues has not been well explored in the urban politics literature. We argue that concerns related to animal welfare are increasingly pressing in many cities yet sustained attention to them appears absent from the urban policy agenda. Using the multiple streams approach, this research examines animal welfare policy in the urban context and suggests why this policy area appears not to have gained a consistent place on the public agenda. Based on a content analysis of media reporting in the Detroit metropolitan area it appears that policy entrepreneurs were unable to access the public agenda through the policy window opened by a major focusing event because of conflicting narratives about the nature of the problem, dissension among policy entrepreneurs themselves, and a lack of debate about potential policy solutions.